Resveratrol amplifies the anti-tumor effect of α-PD-1 by altering the intestinal microbiome and PGD2 content - Baohua Luo; Qingling An; Jingyu Lei; Dengxu Tan; Xiaoqiu Liu; Hui Li; Yong Zhao; Jing Qin; Caiqin Zhang; Yongbin Zhang; Changhong Shi (Gut Microbes)
Patients with pancreatic cancer (PC) receive limited benefits from immune checkpoint inhibitors (ICIs) alone. Recent studies have indicated that the combination of intestinal microflora regulators and ICI may be an effective strategy for enhancing the response to tumor immunotherapy. Resveratrol has been shown to regulate both intestinal microbiota and the immune microenvironment; therefore, we speculated that resveratrol may enhance the immunotherapeutic effect of α-PD-1 on PC. We constructed a double-humanized mouse model with both a humanized immune system and PC to evaluate the efficacy of different doses of resveratrol combined with anti-PD-1 mAb therapy and analyze the characteristics of the tumor immune microenvironment after treatment. In addition, I6S sequencing was performed on mouse fecal samples, and metabolomic analyses were performed on plasma samples to understand the characteristics of the intestinal microbiome and metabolites to explore the potential mechanism of anti-tumor immunity mediated by combined immunotherapy. Results suggested that the combination of resveratrol with anti-PD-1 mAb promoted the infiltration and activation of CD8+ T cells in tumor tissues, thus effectively inhibiting PC growth. Attentively, the effect emphasized the combined effect, dose-dependent nature and the involvement of gut microbiome. Furthermore, metabonomics showed that the combination therapy significantly increased the abundance of the metabolite prostaglandin D2 (PGD2), which was most likely related to the increased abundance of Desulfovibrio fairfieldensis. Finally, we confirmed that PGD2 amplified anti-tumor effect of α-PD-1 by activating prostaglandin D receptor 1 (DP1) to promote CD8 infiltration in double humanized PC mice and subcutaneously transplanted KPC mice. Overall, our data revealed resveratrol has the potential to enhance the efficacy of α-PD-1 by regulating the gut microbiome and its metabolites, and PGD2 was an effective molecular mediating the infiltration of CD8+T cells into tumor tissue to amplify the anti-tumor effect of α-PD-1.Significance The anti-PD-1 mAb may be further considered along with PGD2 or active molecules that can promote PGD2 synthesis to enhance the anti-tumor immune response